Human Resource Projects - Three, ITM-OM Team; Sorooshian, Shahryar; Azizan, Noor Azlinna Binti (Journal of Management and Science, 2013)
This letter is a review article to study basics human resource management, for a class activity in Operations management tutorial under University Malaysia Pahang Undergraduate Programs. In this paper a team of students as their tutorial work studied researches to find what the role of manager of good and service design is.